Pengaruh Harga dan Kualitas Pelayanan Terhadap Kepuasan Pelanggan di Bengkel Djody Motor - Lukman, Djody Julianto Taufik; Fadli, Uus MD; Suherman, Enjang (Jurnal Ilmiah Wahana Pendidikan, 2024)
This study aims to examine the effect of Price and Service Quality on Customer Satisfaction. This research design uses a quantitative method on the customer population of Djody Motor workshop from August 2022 to December 2022 totaling 134 people with a sample of 100 consumers based on the Slovin formula with an error rate of 5%. Data collection through a Google form questionnaire was processed using SPSS 22.0. The results of the study showed that the effect of price on service quality was 89%, which means it has a very strong and positive relationship, the effect of price on customer satisfaction was 39.3%, service quality on customer satisfaction was 36%, the results of the analysis of price and service quality had a simultaneous effect on customer satisfaction of 53.58%.